PELATIHAN SIAGA SEHAT JIWA TERHADAP PENINGKATAN PENGETAHUAN KADER DI RW 06 DAN RW 07 DESA ROWOSARI KECAMATAN TEMBALANG KOTA SEMARANG - Eni Hidayati; Khoiriyah -; Muhammad Fatkul Mubin (Universitas Muhammadiyah Semarang, 2015)
Mental health programs in the area of Semarang is still less than optimal health centers in empowerment, mental health problems have the iceberg. Seeing the development of the current era, it is possible the number of people with mental disorders will increase and more diverse kind. Mental health problems have iceberg. Seeing the development of the current era, it is possible the number of people with mental disorders will increase and more diverse kind. Development of mental health in the Village District Tembalang Rowosari Semarang City has not run optimally. Health cadres in RW 06 and RW 07, said that only limited Posyandu activities posyandu in infants. This causes no detection of mental health in terms of mental disorders, psychosocial and mental health risks, the main objective the establishment of mental health cadres is to improve the quality of life of every citizen to a healthy soul in RW 06 and RW 07 Rowosari Village District Tembalang Semarang. Plan includes training activities carried prongram standby RW healthy soul, detection training healthy family life, families with mental disorders, families with psychosocial risk, families with mental health, mental health counseling, therapeutic group activities, home visit. The approach taken is with intensive discussions, simulation / demonstration skills, role play and visit the house. Evaluation is done by comparing the pre and post test results on any ongoing training. Knowledge and skills of cadres increased in eight training organized team.Keywords : Cadre , RW , alert mental health